Psychological Research Of Coaching Activities In Sports (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Annotation: Physical education and sport psychologist psychological science field as a physical education and sports special conditions business compliance person a psychologist, psixik quality of the formation, development and reflection bo‘lish of qonuniyat of the studyof lish about the concepts given.